2016
DOI: 10.1073/pnas.1615581113
|View full text |Cite
|
Sign up to set email alerts
|

Urban park soil microbiomes are a rich reservoir of natural product biosynthetic diversity

Abstract: Numerous therapeutically relevant small molecules have been identified from the screening of natural products (NPs) produced by environmental bacteria. These discovery efforts have principally focused on culturing bacteria from natural environments rich in biodiversity. We sought to assess the biosynthetic capacity of urban soil environments using a phylogenetic analysis of conserved NP biosynthetic genes amplified directly from DNA isolated from New York City park soils. By sequencing genes involved in the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
100
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 36 publications
0
100
1
Order By: Relevance
“…PCA may also influence the composition and biogeochemical behaviour of soil microbial communities through its antibiotic activity (Mavrodi et al, 2011) or through its utilization as a C and N source (Costa et al, 2015). Multiscale comparisons of the soil organic matter pools (e.g., Redmile-Gordon et al, 2014;Dohnalkova et al, 2017), soil physical properties (e.g., Amellal et al, 1998;Colica et al, 2014) and microbial communities (e.g., Charlop-Powers et al, 2016) that develop in the presence and absence of PCA are necessary to establish these potential impacts upon soil and crop health in dryland wheat fields of the Columbia Plateau.…”
Section: Implications For Agro-ecosystemsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCA may also influence the composition and biogeochemical behaviour of soil microbial communities through its antibiotic activity (Mavrodi et al, 2011) or through its utilization as a C and N source (Costa et al, 2015). Multiscale comparisons of the soil organic matter pools (e.g., Redmile-Gordon et al, 2014;Dohnalkova et al, 2017), soil physical properties (e.g., Amellal et al, 1998;Colica et al, 2014) and microbial communities (e.g., Charlop-Powers et al, 2016) that develop in the presence and absence of PCA are necessary to establish these potential impacts upon soil and crop health in dryland wheat fields of the Columbia Plateau.…”
Section: Implications For Agro-ecosystemsmentioning
confidence: 99%
“…Soil microbes influence nutrient dynamics and plant health through the release of potent metabolites including siderophores (Loper and Buyer, 1991;Schalk et al, 2011;Ahmed and Holmstrom, 2014), surfactants (de Souza et al, 2003;Fechtner et al, 2011;Alsohim et al, 2014;Zeriouh et al, 2014) and natural antibiotics (Haas and Defago, 2005;Mavrodi et al, 2011;Charlop-Powers et al, 2016). Phenazine-1-carboxylic acid (PCA) is a redoxactive antibiotic that has been extensively studied for its activity against fungal plant pathogens ( Thomashow and Weller, 1988;Mavrodi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Exotic areas, usually in regions of the planet minimally impacted by people and with high biodiversity, such as rainforests or coral reefs, are most often explored for natural sources of next-generation antibiotics. CharlopPowers et al (1) extracted DNA from the environment, followed by high-throughput sequencing of its genetic instructions, to reveal that your local park is an untapped resource with enormous potential for discovery of new therapeutics. Additionally, it is a lot easier to get to than a rainforest or a reef.…”
mentioning
confidence: 99%
“…It would be of great interest to test for relationships between the gene clusters coding for antibiotic NRPS or PKS in eDNA and the occurrence rate of clinical antibiotic resistance in the area. If such relationships exist, then understanding patterns of the presence of antibiotic biosynthetic machineries, as shown by Charlop-Powers et al (1), could perhaps one day be used to guide antibiotic use in the clinic based on geography, avoiding antibiotics for which resistance genes can be found in a nearby park (or garden or decorative plant's soil, which is not studied here but is potentially important) and where they might be tracked in on shoes and moved to clinically relevant strains via horizontal gene transfer.…”
mentioning
confidence: 99%
“…Interestingly, soil samples S1–S2 and S10–S18, collected within close geographic proximity from the Yunnan‐Kweichow plateau, still possessed great β ‐diversity, in comparison to samples collected 1000‐km away. This may be attributed to the microenvironment difference in individual sampling sites (Charlop‐Powers et al ., ). The NMDS analysis suggested that differences in sampling sites do not directly correlate to the differences in β‐ diversity of HCS genes (Fig.…”
Section: Resultsmentioning
confidence: 97%